HBR's 10 must reads on teams - St. John, Gregory; Larkin, Susan (HBR's 10 must reads series, 2022)
Most teams underperform. Yours can beat the odds. If you read (or listen) to nothing else on building better teams, listen to these ten articles. We've combed through hundreds of articles in the Harvard Business Review archive and selected the most important ones to help you assemble and steer teams that get results. Leading experts such as Jon Katzenbach, Teresa Amabile, and Tamara Erickson provide the insights and advice you need to: boost team performance through mutual accountability; motivate large, diverse groups to tackle complex projects; increase your teams' emotional intelligence; prevent decision deadlock; extract results from a bunch of touchy superstars; and fight constructively with top-management colleagues.